Ząb dwoisty i nadliczbowy przyczyną opóźnionego wyrzynania zębów 21 i 22 = Dual and supernumerary tooth as a cause of delayed dentition of teeth 21 and 22 - Ratajek-Gruda, Monika; Białkowska-Głowacka, Jolanta; Janas-Naze, Anna (Journal of Education, Health and Sport, 2016)
Ratajek-Gruda Monika, Białkowska-Głowacka Jolanta, Janas-Naze Anna. Ząb dwoisty i nadliczbowy przyczyną opóźnionego wyrzynania zębów 21 i 22 = Dual and supernumerary tooth as a cause of delayed dentition of teeth 21 and 22. Journal of Education, Health and Sport. 2016;6(6):308-317. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.55605 http://ojs.ukw.edu.pl/index.php/johs/article/view/3581 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 10.06.2016. Ząb dwoisty i nadliczbowy przyczyną opóźnionego wyrzynania zębów 21 i 22 Dual and supernumerary tooth as a cause of delayed dentition of teeth 21 and 22 Monika Ratajek-Gruda, Jolanta Białkowska-Głowacka, Anna Janas-Naze Zakład Chirurgii Stomatologicznej UM w Łodzi Kierownik dr hab. n. med. prof. nadzw. Anna Janas-Naze Dr n. med. Monika Ratajek-Gruda, Dr n. med. Jolanta Białkowska-Głowacka, Prof. nadzw. dr hab. n. med. Anna Janas-Naze Zakład Chirurgii Stomatologicznej UM ul. Pomorska 251 92-213 Łódź email: mogruda@wp.pl Praca finansowana przez UM w Łodzi w ramach działalności statutowej nr 503/2-163-01/503-21-001. Streszczenie W pracy przedstawiono przypadek 10 letniego chłopca, u którego stwierdzono jednocześnie 2 zęby zatrzymane, ząb nadliczbowy i zęby dwoiste. Hasła indeksowe: opóźnione wyrzynanie, ząb nadliczbowy, zęby dwoiste. Summary In the study a case of 10 years old boy with 2 impacted teeth, supernumerary tooth and dual teeth was presented. Key words: delayed dentition, supernumerary tooth, dual teeth.